Frontispiece: BIII 5‐Arylsubporphyrins and BIII Subporphine. Issue 72 (20th December 2018) - Kise, Koki; Yoshida, Kota; Kotani, Ryota; Shimizu, Daiki; Osuka, Atsuhiro
Abstract : B III subporphine, shape of which looks like simple triangle‐shaped Japanese rice ball, has been synthesized for the first time together with B III 5‐arylsubporphyrins. All substitution patterns of meso ‐phenyl subporphyrins have been explored. In their UV/Vis absorption spectra, the Soret‐like bands are progressively blue‐shifted as the removal of meso‐phenyl group. Notably, compared with other meso‐phenyl subporphyrins, B III subporphine possesses unique features, such as small Stokes shift, clear vibronic structure in optical spectra, and symmetry of molecular orbitals. For more information, see the Communication by A. Osuka et al. onpage 19136 ff.